2016
DOI: 10.1515/cclm-2015-0953
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin as a potential risk biomarker for cardiovascular and metabolic diseases

Abstract: Clear evidence supports a role for circulating and locally-produced osteocalcin (OC) in the pathophysiology of cardiovascular (CV) lesions and CV risk, also in combination with metabolic changes, including type 2 diabetes mellitus (T2DM). Reduced plasma OC levels are associated with greater incidence of pathological CV changes, like arterial and valvular calcification, coronary and carotid atherosclerosis and increased carotid intima-media thickness. The actual relationship between OC levels and incidence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
2
29
0
1
Order By: Relevance
“…Conflicting results are available concerning plasma OC as a predictor of cardiovascular diseases and related mortality. In general, low circulating OC concentrations were found to be associated with an increased risk of cardiovascular diseases [16, 28, 29]. In agreement with our findings inverse relationship was also seen between the risk of cardiovascular events and plasma OC levels in patients on regular HD suggesting a vasculo-protective role for OC [26, 30, 31].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Conflicting results are available concerning plasma OC as a predictor of cardiovascular diseases and related mortality. In general, low circulating OC concentrations were found to be associated with an increased risk of cardiovascular diseases [16, 28, 29]. In agreement with our findings inverse relationship was also seen between the risk of cardiovascular events and plasma OC levels in patients on regular HD suggesting a vasculo-protective role for OC [26, 30, 31].…”
Section: Discussionsupporting
confidence: 88%
“…Depending on the extent of its carboxylation several isoforms are formed and released into the circulation that have different biological activities including the regulation of VC and atherosclerosis, as well as the modulation of insulin secretion and insulin sensitivity. Importantly, OC is also expressed in the calcified atherosclerotic lesion where it may modulate this process [16, 23-25]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients evaluated in this study, in fact, displayed an acute vascular event which was the result of inflammation-related processes and alteration in the composition of the media tunica of the vascular wall. Recent reports indicated that OC is associated to arterial diseases, thus being a molecule able to exert important effects also on vascular tissues which is similar to bone tissue in term of regulation of mineral homeostatsis [21]. In addition to OC, another molecule mainly produced by the bone, osteopontin, emerged as a novel player in arterial remodeling, inflammation, and the promotion of fibrosis, thus suggesting the same ability of these bone-derived molecules to target the cardiovascular system [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…OC exists in two main form: carboxylated, promoted by vitamin K, and undercarboxylated. In this latter form, it has less affinities towards calcium and hydroxyapatite and it is easily secreted and plays important endocrine activities, such as the stimulation of insulin secretion, the increase in insulin sensitivity, and the reduction of blood glucose levels [21]. Both forms are anyway secreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation